2004
DOI: 10.1002/ajh.20203
|View full text |Cite
|
Sign up to set email alerts
|

Type I Gaucher disease with severe skeletal destruction, extraosseous extension, and monoclonal gammopathy

Abstract: Extraosseous extensions of Gaucher-cell deposits simulate malignant diseases. We describe a 65-year-old male with type-I Gaucher disease, confirmed by low leukocyte glucocerebrosidase activity, high plasma chitotriosidase, and N370/L444P gene-mutations, who had severe skeletal involvement, IgG-k monoclonal gammopathy, and a soft-tissue mass within the left iliac muscle. Bone marrow biopsy showed heavy infiltration by Gaucher cells, and histopathology of the excised extraosseous mass revealed infiltration by Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Careful measurement of the mass is required, as the spleen may shrink in response to treatment, making the Gaucheroma appear proportionately larger and thus mimicking a growing tumour. Gaucheromas are common in the spleen and liver ( Patlas et al , 2002 ) and are noted in Gaucher-related skeletal disease ( Kaloterakis et al , 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Careful measurement of the mass is required, as the spleen may shrink in response to treatment, making the Gaucheroma appear proportionately larger and thus mimicking a growing tumour. Gaucheromas are common in the spleen and liver ( Patlas et al , 2002 ) and are noted in Gaucher-related skeletal disease ( Kaloterakis et al , 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…A postulated mechanism for the cortical destruction necessary for extraosseous extension is the release of hydrolases and cytokines due to increased intramedullary pressure [3]. All four cases of extraosseous Gaucher disease found by Poll et al [3] as well as two cases reported by Hermann et al [5] and a case reported by Kaloterakis et al [8] described underlying marrow involvement and cortical disruption. To our knowledge, our patient is the only reported case of a subcutaneous Gaucher cell mass without extension from adjacent bone or lymph nodes.…”
Section: Discussionmentioning
confidence: 93%
“…The disease is characterized by a deficiency of beta-glucocerebrosidase, which in turn leads to accumulation of glucocerebrosides (specifically glucosylceramide). Glucocerebroside-laden macrophages known as Gaucher cells typically accumulate in the liver, spleen, bone marrow, lymph nodes, brain, and lung [1][2][3][4][5][6][7][8][9]. Bone marrow involvement with Gaucher disease is particularly common, being a major complication in up to 80 % of affected patients and can result in anemia, coagulopathy, osteonecrosis, bony remodeling, and fracture [3,4].…”
Section: Introductionmentioning
confidence: 98%
“…GBA gen is located in chromosome 1q21 [2]. Three types of this autosomal recessive disorder have been described based on the presence and nature of the central nervous system involvement [3,4]. Type 1 (or chronic non-neuronopathic GD) is the most common form of the disease, type 2 (or acute infantile neuronopathic GD) typically begins within 6 months of birth, and type 3 (or chronic neuronopathic form) may begin at any time in childhood or even in adulthood [5,6].…”
Section: Introductionmentioning
confidence: 99%